TO ASSESS THE KNOWLEDGE, ATTITUDE AND PERCEIVED BARRIERS OF CRITICAL CARE NURSES ON PAIN MANAGEMENT OF CRITICALLY ILL PATIENTS IN TERTIARY CARE HOSPITAL - SIDDIQUE , I; SADDIQUE , H; JABEEN , R (Biological and Clinical Sciences Research Journal, 2024)
Effective pain management is a cornerstone of critical care, ensuring comfort and optimizing recovery for critically ill patients. In Pakistan, critical care nurses play a pivotal role in pain management; however, knowledge gaps, misconceptions, and systemic barriers hinder optimal practice. Objective: To assess the knowledge, attitudes, and perceived barriers of critical care nurses regarding pain management of critically ill patients in a tertiary care hospital in Lahore, Pakistan. Methods: A descriptive cross-sectional study was conducted among 126 critical care nurses using a structured questionnaire. Data on demographics, knowledge, attitudes, and barriers to pain management were analyzed using descriptive statistics. Results: Only 19.8% of nurses had good knowledge of pain management, while 42.9% had average knowledge, and 37.3% had poor knowledge. Negative attitudes were prevalent among 76.2% of participants, including misconceptions about opioid use and pain assessment methods. The most commonly reported barriers were insufficient knowledge (52.4%) and inadequate experience (23.0%), along with time constraints (4.0%) and inadequate pain assessment practices (19.0%).Conclusion: Significant gaps in knowledge, attitudes, and systemic barriers hinder effective pain management among critical care nurses in Pakistan. Targeted training programs and systemic reforms are essential to address these challenges and enhance pain management outcomes in critical care settings.